Diagnostic value of breast ultrasound in mammography BI-RADS 0 and clinically indeterminate or suspicious of malignancy breast lesions - Dobrosavljevic, Aleksandar Z; Rakić, Snežana; Nikolić, Branka; Janković Ražnatović, Svetlana; Dragojević Dikić, Svetlana; Milošević, Zorica; Jurišić, Aleksandar; Skrobić, Milica (Vojnosanitetski pregled, 2016)
Background/Aim. Not only that ultrasound makes the difference between cystic and solid changes in breast tissue, as it was the case at the beginning of its use, but it also makes the differential diagnosis in terms of benign-malignant. The aim of this study was to assess the role of sonography in the diagnosis of palpable breast masses according to the American College of Radiology Ultrasonographic Breast Imaging Reporting and Data System (BI-RADS) and  to correlate the BI-RADS 4 and BI-RADS 5 category with pathohistological findings. Methods. A retrospective study was conducted with the breast sonograms of 30 women presented with palpable breast masses found to be mammography category  BI-RADS 0 and ultrasonographic BI-RADS categories  4 and 5. The sonographic categories were correlated with pathohistological findings. Results. Surgical biopsy in 30 masses revealed: malignancy (56.7%), fibroadenoma (26.7%), fibrocystic dysplasia with/without atypia (10%), lipoma (3.3%) and intramammary lymph node (3.3%). Correlation between BI-RADS categories and pathohistological findings was found (p < 0.05). All BI-RADS 5 masses were malignant, while in BI-RADS 4A category fibroadenomas dominated. A total of 53.8% of all benign lesions were found in women 49 years of age or younger as compared with 35.3% of all malignancies in this group (p < 0.05). Conclusion. Ultrasonography BI-RADS improved classification of breast masses. The ultrasound BI-RADS 4 (A, B, C) and BI-RADS 5 lesions should be worked-up with biopsy.
Keywords: breast neoplasms; diagnosis; differential; mammography; ultrasonography; doppler; color; predictive value of tests; risk assessment